SOME WI-FI ACCESS POINTS IN THE CITY OF SOFIA (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The purpose of this article is to present the results of a study of the number and type of Wi-Fi access points using applications for the collection, processing and analysis of data based on a sample collected in different areas and places with a significant concentration of people in a city Sofia, Bulgaria. Data on the number and type of access points were obtained by measurements taken at the respective locations. User equipment connects to different Wi-Fi access points located in different places in the city that are accessible. Data was collected for wireless access points that are fourth and fifth generation. Different generations in wireless networks have corresponding download and upload speeds and frequencies. In the article, the results are grouped and analyzed according to different characteristics.